N‐methylmesoporphyrin IX fluorescence as a reporter of strand orientation in guanine quadruplexes. (26th February 2014) - Sabharwal, Navin C.; Savikhin, Victoria; Turek‐Herman, Joshua R.; Nicoludis, John M.; Szalai, Veronika A.; Yatsunyk, Liliya A.
<x xml:space="preserve">Abstract</x> Guanine quadruplexes (GQ) are four‐stranded DNA structures formed by guanine‐rich DNA sequences. The formation of GQs inhibits cancer cell growth, although the detection of GQs in vivo has proven difficult, in part because of their structural diversity. The development of GQ‐selective fluorescent reporters would enhance our ability to quantify the number and location of GQs, ultimately advancing biological studies of quadruplex relevance and function. N‐methylmesoporphyrin IX (NMM) interacts selectively with parallel‐stranded GQs; in addition, its fluorescence is sensitive to the presence of DNA, making this ligand a possible candidate for a quadruplex probe. In the present study, we investigated the effect of DNA secondary structure on NMM fluorescence. We found that NMM fluorescence increases by about 60‐fold in the presence of parallel‐stranded GQs and by about 40‐fold in the presence of hybrid GQs. Antiparallel GQs lead to lower than 10‐fold increases in NMM fluorescence. Single‐stranded DNA, duplex, or i‐motif, induce no change in NMM fluorescence. We conclude that NMM shows promise as a 'turn‐on' fluorescent probe for detecting quadruplex structures, as well as for differentiating them on the basis of strand orientation.